Generation Y on the labour market - expectations for shaping the work-life balance - Elzbieta Robak (Institute of Economic Research (IER), 2017)
Entering of the generation Y on job market causes many interesting insights for both researchers, who analyze the specifics of this generation, as well as practitioners of modern organizations' management. Despite some differences in the characteristics of generation Y authors involved in this issue agree that generation Y is focused on education and development with simultaneous desire to maintain a balance between work and personal life. More often than older generations, they are willing to use the various programs, offered by company, supporting reconciliation of professional and personal life. The aim of the article is to present issues concerning the functioning of the representatives of generation Y in the labor market with particular emphasis on the issue of balancing professional work and personal life. The conducted research aimed to analyze the opinion of representatives of generation Y about the expectations associated with their professional work with special emphasis on creating a balance between work and personal life. In order to obtain answers to the research's questions method of diagnostic survey and questionnaire technique were used. To complement the obtained data, the additional qualitative research unstructured interviews were conducted. Respondents confirmed the hypothesis that for their generation balance between work and personal life is very important. The collected respondents' opinions showed the image of flexible employment, as a good way to reconcile work and other obligations, which gives the ability to have multiple sources of income and that is a good solution especially for young people and people entering the labor market. The results of the conducted interviews pointed to a number of factors, that in opinion of young workers are important values in life and are related to the maintaining work-life balance.
Keywords: J53; J62; 330; generation Y; labour market; work-life balance; relationships in the workplace